Comparisons of nutrient status between regular season and off-season cropping of Curcuma alismatifolia Gagnep - S. Ruamrungsri (2018)
The present work investigated the nutrient status in plant tissue and plant growth between regular season (RS) and off-season (OS) cropping of Curcuma alismatifolia Gagnep. at flowering stage. To use this species for year-round cut flower or rhizomes production it was necessary to establish adequate cultivation techniques. The determination of nitrogen (N), phosphorous (P) and potassium (K) status in plants is basic information that can be used to evaluate the optimum crop fertilizer requirement. At flowering stage (12 weeks after planting: WAP), the nutrient contents in plant component and plant growth of Curcuma plants under the different cropping systems were analysed. N content in old rhizomes, old storage roots and new rhizomes was significantly increased under the OS cropping, but the opposite result was found in leaves. The highest N content was observed in leaves under RS condition (353.23 mg plant-1). Higher P content was found in leaves and inflorescence under the RS cropping (87.95 and 60.84 mg plant-1), while RS cropping tissue contained less P content in new rhizomes (9.68 mg plant-1). K content significantly decreased in leaves, old rhizomes and new rhizome under the OS cropping (228.26, 14.19 and 2.11 mg plant-1). The OS cropping system resulted in reduced N, P and K content in most aboveground organs, increased dry matter accumulation in below ground organs (old storage roots, new rhizomes and new storage roots) and decreased dry matter accumulation in leaves and inflorescences. Poor quality of plant (decrease in height, canopy and total leaves areas) was also found in OS cropping.